Detailed Photoisomerization Dynamics of a Green Fluorescent Protein Chromophore Based Molecular Switch. (3rd September 2014) - Jiang, Chen-Wei; Fang, Ai-Ping; Zhao, Di; Li, Hong-Rong; Xie, Rui-Hua; Li, Fu-Li
Abstract : With density-functional-based nonadiabatic molecular dynamics simulations, trans -to- cis and cis -to- trans photoisomerizations of a green fluorescent protein chromophore based molecule 4-benzylidene-2-methyloxazol-5(4H)-one (BMH) induced by the excitation to its S 1 excited state were performed. We find a quantum yield of 32% for the trans -to- cis photoisomerization of BMH and a quantum yield of 33% for its cis -to- trans photoisomerization. For those simulations that did produce trans -to- cis isomerization, the average S 1 excited state lifetime of trans -BMH is about 1460 fs, which is much shorter than that of cis -BMH (3100 fs) in those simulations that did produce cis -to- trans isomerization. For both photoisomerization processes, rotation around the central C2=C3 bond is the dominant reaction mechanism. Deexcitation occurs at an avoided crossing near the S 1 /S 0 conical intersection, which is near the midpoint of the rotation.